Analysis of Spatial Development in and Around the City of Isparta through Remote Sensing and Geographic Information Systems - Temurçin, Kadir; Uluşar, Gizem (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
Remote Sensing is a method of examination used in the study of resources on earth without any physical contact. It is a method by which the characteristics of the land below are recorded from space and sky. Determining the characteristics of natural and cultural resources of earth, sustainable exploitation of these resources in the most effective ways and continuous monitoring of the changes in these resources are fundamental to being a developed country. For a sustainable land use and urbanization, data about the unstable natural environment must be collected and monitored at regular intervals, and in order to do these, Remote Sensing (RS) and Geographical Information Systems (GIS) are employed. Images obtained through RS method can be analyzed for the accurate use of the data available. This study seeks to determine the spatial development in and around the city of Isparta through digital imaging processing techniques on different satellite images which belong to different years. Images from satellites ASTER and LANDSAT; information on the quarters in Isparta and the city plan and ERDAS IMAGINE 9.1 program were used in the study. The spatial development of the city of Isparta was studied on the basis of the satellite images obtained in the years 1987, 2000 and 2010 and this study was integrated into GIS. Having analyzed how much change occurred and which way it trended, important information was collected which will be used as source for future studies to be carried out on Isparta. It was observed that while residential areas increased, amount of forested land, and agricultural areas decreased during the periods studied.